Dando vida à célula: proposta lúdica para auxiliar o ensino de biologia celular por meio de QR code - Almeida, Wanderley Alves de (2020)
This paper approaches a bibliographic research that intends to suggest the use of the QR Code (Quick Response Code) as a support tool for Science classes in the final years of Elementary School and Biology in High School through a game aimed at teaching cell biology. The theme is justified due to the widespread use of information and Communication Technology in today’s society, especially in such a delicate moment where classes are taking place remotely due to the pandemic of the new Coronavirus outbreak, with smartphones being indispensable items and now they also insert the school environment more than ever experienced in the world. In this way, the objective is an innovative and creative teaching methodology that involves students in a more interactive and meaningfull learning using technology.